Examining the models of religious harmony in anticipating hate polarization in regional head elections in Medan City - Fauzan, Indra; Nasution, Faiz Albar; Regif, Surya Yudha (Research Journal in Advanced Humanities, 2024)
The issue of religious politicization often arises, considering that religious diversity is often used as a political tool to gain majority support. This article aims to analyze the model of religious harmony in anticipating the polarization of hatred in the Regional Head Election in Medan City. This research uses a qualitative research method with a descriptive approach. The data collection techniques used in this research are Focus Group Discussion and library observation. Data analysis techniques through data reduction, display, and conclusion drawing. The results show the significant challenges faced by Medan City regarding religious harmony and polarization of hatred in the context of the Regional Head Election. The contradiction between religious activism, local politics, and democratization has triggered the use of religion as a tool to strengthen certain political interests, causing polarization and hostility among voters. Hate speech and the politicization of religion undermine social harmony and the integrity of local democracy. Nonetheless, efforts are made by the Religious Harmony Forum and religious leaders to promote tolerance and interfaith cooperation. The model of religious harmony in this study highlights educational approaches, interfaith dialogue, and the active role of religious leaders and local government. Lessons from history show that interfaith cooperation can build a harmonious society. The contribution of this research in understanding the dynamics of religious harmony in Medan City is important for further development in promoting tolerance and harmony.